Reduced C9ORF72 function exacerbates gain of toxicity from ALS/FTD-causing repeat expansion in C9orf72 - Zhu, Qiang; Jiang, Jie; Gendron, Tania F.; McAlonis-Downes, Melissa; Jiang, Lulin; Taylor, Amy; Diaz Garcia, Sandra; Ghosh Dastidar, Somasish; Rodriguez, Maria J.; King, Patrick; Zhang, Yongjie; La Spada, Albert R.; et al. (Nature neuroscience, 2020)
Hexanucleotide expansions in C9orf72 , which encodes a predicted guanine exchange factor, are the most frequent genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Although repeat expansion has been established to generate toxic products, mRNAs encoding the C9ORF72 protein are also reduced in affected individuals. In this study, we tested how C9ORF72 protein levels affected repeat-mediated toxicity. In somatic transgenic mice expressing 66 GGGGCC repeats, inactivation of one or both endogenous C9orf72 alleles provoked or accelerated, respectively, early death. In mice expressing a C9orf72 transgene with 450 repeats that did not encode the C9ORF72 protein, inactivation of one or both endogenous C9orf72 alleles exacerbated cognitive deficits, hippocampal neuron loss, glial activation and accumulation of dipeptide-repeat proteins from translation of repeat-containing RNAs. Reduced C9ORF72 was shown to suppress repeat-mediated elevation in autophagy. These efforts support a disease mechanism in ALS/FTD resulting from reduced C9ORF72, which can lead to autophagy deficits, synergizing with repeat-dependent gain of toxicity. The most common genetic cause of ALS and frontal temporal dementia—hexanucleotide repeat expansion in C9orf72 —is shown to provoke disease via synergy of gain of toxicity(ies) from repeat-encoded RNAs/dipeptide repeat proteins and reduction in the C9ORF72 protein.